2020
DOI: 10.1128/aac.00078-20
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics-Pharmacodynamics of Enmetazobactam Combined with Cefepime in a Neutropenic Murine Thigh Infection Model

Abstract: Third-generation cephalosporin (3GC)-resistant Enterobacteriaceae are classified as critical priority pathogens, with extended-spectrum β-lactamases (ESBLs) as principal resistance determinants. Enmetazobactam (formerly AAI101) is a novel ESBL inhibitor developed in combination with cefepime for empirical treatment of serious Gram-negative infections in settings where ESBLs are prevalent. Cefepime-enmetazobactam has been investigated in a phase 3 trial in patients with complicated urinary tract infections or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…An example of a β-lactam inhibitor is enmetazobactam, which is a penicillanic acid sulfone currently developed in combination with cefepime. 92,93 This combination was found to be effective against OXA-48 producers, but the efficacy is most likely again attributed to the activity of cefepime and not to efficient inhibition by enmetazobactam, which is active primarily against ESBLs. 93,94 On the other hand, boronates show promise as broad-spectrum β-lactamase inhibitors.…”
Section: Neutralmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of a β-lactam inhibitor is enmetazobactam, which is a penicillanic acid sulfone currently developed in combination with cefepime. 92,93 This combination was found to be effective against OXA-48 producers, but the efficacy is most likely again attributed to the activity of cefepime and not to efficient inhibition by enmetazobactam, which is active primarily against ESBLs. 93,94 On the other hand, boronates show promise as broad-spectrum β-lactamase inhibitors.…”
Section: Neutralmentioning
confidence: 99%
“…92,93 This combination was found to be effective against OXA-48 producers, but the efficacy is most likely again attributed to the activity of cefepime and not to efficient inhibition by enmetazobactam, which is active primarily against ESBLs. 93,94 On the other hand, boronates show promise as broad-spectrum β-lactamase inhibitors. In particular, cyclic boronates can act as analogues of the tetrahedral acylation transition state of SBLs, 95 and have potential for at least moderate activity against MBLs.…”
Section: Neutralmentioning
confidence: 99%
“…The correlation between the host, pathogens, and the drug is usually determined via the neutropenic mice thigh infection model [ 10 , 11 ]. The stability, maturity, and avoidance of the host immune system’s impact on the antibacterial effect are all major advantages of this model.…”
Section: Introductionmentioning
confidence: 99%
“…In accord with prior studies ( 20 , 34 ), we observed only small differences in potency for enmetazobactam compared to the closely related tazobactam ( SI Appendix , Tables S1–S3 ). The reported significantly enhanced potential of enmetazobactam against class A ESBLs in cells ( 33 , 34 ) and in vivo ( 41 ) may thus result from improved properties with respect to variables other than potency against isolated SBLs, e.g., outer membrane permeability or efflux pump susceptibility.…”
Section: Discussionmentioning
confidence: 99%